The demarcation between crimes as money laundering and budget fraud in regard to the untaxed excise products (Academic Journal of Internal Affairs, 2021)
The amendment of the Criminal Code to come into effect from 1st of January 2021 transferred receiver behavior to the facts of money laundering and repealed receiving as an independent fact. As a result of the amendment to the law, it is also possible to establish the behaviors defined in the second case of budget fraud and in the fourth case of money laundering concerning the untaxed excise products. This fact makes it essential to the investigative authorities to determine and demarcate the relationship between the matter of facts. The present study, since the prevailing jurisprudence and unified official position are not available at the time of its preparation, intends to present the legal and professional arguments of the demarcation – in a criticism-tolerant approach – which can be a possible starting point for a later permanent, unified interpretation of the law.
Keywords: aggregation; excise goods; budget fraud; receiving (of stolen goods)